Temporal variations of length, weight and condition of the Asian stinging catfish Heteropneustes fossilis (Bloch, 1794) in the Ganges river (NW Bangladesh) - Parvin, Most Farida; Hossain, Md Yeamin; Rahman, Md Ashekur; Sarmin, Most Shakila; Ahmed, Zoarder Faruque (Research in Agriculture Livestock and Fisheries, 2021)
The present study revealed on temporal variations of length, weight and condition of Heteropneustes fossilis (Bloch, 1794) in the Ganges River, Northwestern Bangladesh. Total 1161 individuals of H. fossilis were caught by various habitual fishing gears such as seine net, cast net and gill net during January to December 2019. For every specimen, body weight (BW) was taken by digital balance to the accuracy of 0.01 g and total length (TL) was taken using a measuring board. Relative condition factor (KR) was assessed by KR = W/(a×Lb), where W is the BW in g, L is the TL in cm and a and b are length-weight relationships parameters. The value of KR ~ 1 specifies good health, >1 specifies over bodyweight as compared to length, whereas <1 suggests a fish in poor condition. The TL varied from 8.5-28.7 cm whereas the BW was 37.17–2250 g. The overall KR for H. fossilis was 0.99-1.06 in the Ganges River. The highest KR was observed in May while the lowest was in January. The KR was significantly correlated with BW in the Ganges River. The outcomes of the study will be helpful for future management of this fish in the Ganges river ecosystem as well as adjacent water bodies. Res. Agric., Livest. Fish.8(2): 259-266, August 2021